Effectiveness of HIPO Android-based application in improving hypertension self-management literacy among obese patients - Ros Endah Happy Patriyani; Sunarsih Rahayu (International Journal of Public Health Science (IJPHS), 2026)
Hypertension in obese patients requires comprehensive management through enhanced health literacy. Android-based applications represent a promising innovation for improving hypertension control literacy. To analyze the effectiveness of the Android-based hypertension and obesity information system (HIPO) application in improving hypertension control literacy among obese patients. This quasi-experimental study employed a one-group pretest-posttest design without a control group, conducted at Sibela Community Health Center, Surakarta, from June to December 2025. Seventy-six respondents were selected through purposive sampling, meeting criteria of primary hypertension (≥ 140/90 mmHg) and BMI ≥ 25 kg/m². The intervention involved four weeks of HIPO application use. Data were analyzed using the Wilcoxon Signed Rank Test. Respondents were predominantly female (67.11%), aged 46-55 years (31.58%), with a genetic predisposition to hypertension (57.89%). Systolic blood pressure significantly decreased from 159.53 ± 14.19 to 144.48 ± 11.44 mmHg (p < 0.001), and diastolic from 95.20 ± 6.55 to 88.50 ± 4.58 mmHg (p < 0.001). Good knowledge increased from 35.53% to 55.26%, and good hypertension control increased from 35.53% to 61.84%. The HIPO application significantly improved blood pressure, knowledge, and hypertension control. However, the absence of a control group limits causal inference. This application may serve as a supplementary educational tool in primary healthcare chronic disease management programs.